Konsep Kebahagiaan Perspektif Islam Dalam Al-Qurán - Alisa Chusuma Dewi; Muhammad Saiful Hidayat (Ikhlas : Jurnal Ilmiah Pendidikan Islam, 2024)
The purpose of this research is to investigate and evaluate the meaning of happiness as it is presented in the Qur'an and to determine the aspects that, from an Islamic standpoint, affect achieving happiness. It is anticipated that this study will make numerous contributions. giving readers a more thorough grasp of the Islamic definition of happiness so that it might serve as a model for scientific advancement, particularly in the areas of positive psychology and religious studies. making contributions to the creation of educational and self-improvement initiatives grounded in the Qur'anic principles. Every human being has the common need to be happy. A thorough grasp of the notion of happiness is provided for Muslims who look to the Qur'an as their source of life direction. The study's findings can be used in a variety of contexts, including teaching, counseling, and therapy. The Qur'anic definition of happiness can serve as the foundation for intervention initiatives designed to enhance the well-being of both people and society.